Inhibitory processes in toddlers: a latent-variable approach - Gandolfi, Elena; Viterbori, Paola; Traverso, Laura; Usai, M. Carmen (Frontiers in Psychology, 2014)
The aim of this study was to investigate the nature of inhibitory processes in early childhood. A confirmatory factor analysis was used to examine the latent structure of inhibitory processes in day-care center children aged 24–32 months and in preschool children aged 36–48 months. The best fit to the data for the younger sample was a single undifferentiated inhibition factor model; in older children, a two-factor model was differently identified in which response inhibition and interference suppression were distinguished.